(untitled) (Revista Contexto & Educação, 2026)
This article analyzes the perceptions of scholarship recipients who participated in projects supported by the National Council for Scientific and Technological Development (CNPQ) and the Ministry of Science, Technology, and Innovation (MCTI) Call for Proposals, launched in 2018 and entitled Girls in the Exact Sciences, Engineering, and Computing. This call was part of the Women and Science program and aimed to encourage female students to choose careers in the exact sciences, engineering, and computing, as well as to reduce student dropout rates in these programs. This article aims to demonstrate how public policies can change aspirations or projections about female students and their potential entry into traditionally male-dominated careers, as well as increase self-confidence, self-esteem, feminist networks, break stereotypes, and other topics. The methodology used was to capture these perceptions via an online form, enabling analysis and incorporation of stories, which invites us to deconstruct power relations, question gender norms, and transform cultural concepts and practices.